The Influence of Promotions, Products and Costs on The Decision Making - Khoirul Anwar; Suyitno Suyitno; Umi Nur Afifah; Imriani Idrus; Sri Rahayu (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Decision-making will be influenced by information about interesting information, quality products, and affordable education costs to create someone’s direction and enthusiasm in pursuing higher education so that with this it can help a school institution in increasing the number of students and the services provided to their customers. The research was conducted with the aim to find out how the influence of promotions, products, and education costs on the decision-making of choosing a school. It used a quantitative method with the help of the IBM SPSS version 25 application, tested the validity and reliability of the research instrument, sampling technique used the saturated sample method which took all the population to be sampled, and data collection using a questionnaire. The results of this study indicate that the promotion variable (X1) has an influence on decision-making (Y1), and the product variable (X2) has an influence on decision-making (Y1). It can be seen based on the results of testing the t-test hypothesis where tcount>ttable (2.854 > 1.980) and a significant level that is less than 0.05 (0.024 <0.05), the variable cost of education (X3) has an influence on decision making (Y1).